2021
DOI: 10.1177/03015742211057241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of AdvanSync2® and Twin Block Appliances in Treatment of Class II Malocclusion With Retrognathic Mandible—An Observational Retrospective Study

Abstract: Objectives: To evaluate the treatment outcomes between Twin Block and AdvanSync2® appliances by comparing the skeletal, dentoalveolar, and soft tissue changes. Materials and Methods: Radiographic data of 20 patients were retrospectively analyzed. Data were selected from patients in their skeletal growth spurt as evaluated by the cervical vertebral maturation method (CVMI 2, 3, and 4), with class II malocclusion characterized with retrognathic mandible (ANB > 4°, SNB < 77°, FMA = 25 ± 5°, overjet > 5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…PowerScope utilizes an anterior attachment, whereas AdvanSync2 is situated on molars. Our findings contradict those of a previous study [ 18 ], which reported a substantial decrease in overbite with AdvanSync. It is advisable to employ FFA supported with mini plates to mitigate dental side effects on the lower anterior teeth [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…PowerScope utilizes an anterior attachment, whereas AdvanSync2 is situated on molars. Our findings contradict those of a previous study [ 18 ], which reported a substantial decrease in overbite with AdvanSync. It is advisable to employ FFA supported with mini plates to mitigate dental side effects on the lower anterior teeth [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Both dental appliances achieved mandibular advancement; however, AdvanSync2 demonstrated a greater degree of advancement than PowerScope did. This finding was substantiated by previous research [ 10 , 18 ]. In contrast, some studies have reported contradictory results [ 8 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…The AdvanSync appliance resulted in significant extrusion and retroclination of upper incisor, proclination of lower incisors, improvement in molar relation and overjet. These findings are in agreement with earlier studies that evaluated the dentoalveolar effects of functional appliances [ 13 , 15 - 17 ]. There was an improvement in the facial soft tissue convexity in both Forsus and AdvanSync appliance group in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…This effective result with AdvanSync appliance may be attributed due to the effective full-time wear obtained whereas patient compliance may have been compromised with the Twin Block appliance. There was also reduction in SNA angle which was not significant [ 17 ]. Similar findings were found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In short term, removable functional appliances are effective in improving class II malocclusion. (20)…”
Section: Introductionmentioning
confidence: 99%